CLOSING THE GENDER GAP IN THE MINING SECTOR: THE INCLUSIVE PRACTICES (Journal of International Studies, 2024)
Multinational corporations (MNCs) are increasingly involved in the United Nations Sustainable Development Goals (SDGs) initiative to enhance the quality of life in host countries. Gender equality (SDG 5) is the key focus. This study examines how MNCs in the male-dominated mining industry in Thailand and Laos promote gender equality through their policies and practices. Using a qualitative approach, we investigated the experiences of stakeholders in the mining sector. Our findings reveal significant gender disparities in employment, health, and vocational opportunities. While MNCs are making efforts to address these issues, the complex interplay of stakeholders and cultural factors influences progress. To effectively advance gender equality, this research suggests a shift in focus towards strategies that actively engage women in diverse business roles. Providing women with the necessary skills and knowledge is essential for their growth and empowerment within the mining industry.